2022
DOI: 10.5713/ab.21.0084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a multi-strain probiotic on growth, health, and fecal bacterial flora of neonatal dairy calves

Abstract: Objective: The aim of this study was to investigate the effects of dietary supplementation with a multi-strain probiotic (MSP) product containing of Bifidobacterium animalis, Lactobacillus casei, Streptococcus faecalis, and Bacillus cerevisiae on growth, health, and fecal bacterial composition of dairy calves during the first month of life.Methods: Forty Holstein calves (24 female and 16 male) at 2 d of age were grouped by sex and date of birth then randomly assigned to 1 of 4 treatments: milk replacer supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
6
12
0
Order By: Relevance
“…Adding PF to the calves’ diet caused limited changes within community diversity (α-diversity) from WK0 to WK4, and no statistical differences were observed in the Simpson, Shannon, and Chao1 indices. Our findings are comparable to previous studies on changes in fecal microbiota in calves when fed with multispecies probiotics during the initial eight weeks of life (Wu et al 2021 ; Guo et al 2022 ). It is well documented that GIT bacterial population go through dynamic changes in abundance and diversity with the progressing age of calves (Amin et al 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Adding PF to the calves’ diet caused limited changes within community diversity (α-diversity) from WK0 to WK4, and no statistical differences were observed in the Simpson, Shannon, and Chao1 indices. Our findings are comparable to previous studies on changes in fecal microbiota in calves when fed with multispecies probiotics during the initial eight weeks of life (Wu et al 2021 ; Guo et al 2022 ). It is well documented that GIT bacterial population go through dynamic changes in abundance and diversity with the progressing age of calves (Amin et al 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Prevention and control of NCD outbreaks in young calves before occurring are more cost effective, and current study have found that early intervention of probiotics has a better preventive effect (Wu et al 2021 ). These effects were more pronounced during the first two months of the calf’s birth than in later stages, indicating probiotics are most efficacious in establishing gut microbiomes than stabilized ones (Malmuthuge et al 2015 ; Guo et al 2022 ). Therefore, in-feed supplementation of lactobacilli strains would be expected to maintain a eubiotic state in gut microbial ecology and beneficial in preventing diarrheal episodes in neonatal calves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This beneficial shift was also correlated with enhanced ruminal papilla and small intestinal villus growth of the studied animals. In another study, the effect of a multi-strain probiotic product containing Bifidobacterium animalis , Lactobacillus casei , Streptococcus faecalis , and Bacillus cerevisiae on general health and the fecal bacterial composition of Holstein’s calves were investigated and it was found that although the probiotic supplements did not affect the overall fecal microflora at the phylum level, the relative abundance of beneficial Prevotella increased while abundance of the opportunistic pathogens Dorea decreased ( Guo et al, 2022 ), suggesting that this probiotic supplements supported an enhanced defence mechanism of the rumen and the intestine, potentially reducing the risk of colonization by pathogens.…”
Section: Impact Of Probiotic Microorganisms On Animals’ Welfarementioning
confidence: 99%